The Associations of cerebral blood flow and white matter hyperintensities with tau and amyloid-beta across the Alzheimer’s disease spectrum - Keshuo Lin; Perminder S. Sachdev; Jiyang Jiang (Brain Imaging and Behavior, 2026)
Although the associations between cerebrovascular dysfunctions and Alzheimer’s disease are increasingly appreciated, the relationship of cerebral blood flow and white matter hyperintensities with tau and amyloid-β pathology remains unclear, particularly in the longitudinal context. This study investigated cross-sectional and longitudinal associations of cerebral blood flow and white matter hyperintensities with tau and amyloid-β pathology using multimodal imaging and blood biomarkers in 179 participants from the ADNI3 cohort. Participants underwent structural (T1-weighted, T2-weighted FLAIR) and arterial spin labelling perfusion MRI, tau and amyloid-β PET, and plasma assay tests for amyloid-β 42, amyloid-β 40, and phosphorylated tau-217. Tau from PET was negatively associated with cerebral blood flow both cross-sectionally and longitudinally in the posterior brain, independent of amyloid-β quantified from PET. Higher white matter hyperintensities volumes were associated with higher levels of tau and amyloid-β at baseline, but the associations were significantly attenuated after further adjusting for amyloid-β and tau, respectively. Plasma amyloid-β 42/40 ratio was negatively associated with white matter hyperintensity volumes both cross-sectionally and longitudinally. In conclusion, tau pathology showed spatially specific associations with cerebral hypoperfusion, independent of amyloid-β, particularly in posterior regions. The attenuation of associations of white matter hyperintensities with amyloid-β and tau after adjustment may reflect shared disease-related variance rather than distinct independent effects.